Die Trennung von Carotinoidgemischen durch Gegenstromextraktion (II) - H. Pfander; F. Haller; K. Bernhard; H. Thommen (CHIMIA)
Countercurrent distribution has been used for the separation of β-carotene and its epoxides without rearrangement reactions. The separation of an extract from Carica papaya shows that this method is suitable for the detection of carotenoids which occur in very low concentrations.